Improvement of Walking Distance by Defibrotide in Patients with Intermittent Claudication - Violi, F.; Marubini, E.; Coccheri, S.; Nenci, G. G. (Thrombosis and Haemostasis, 2000)
Defibrotide is an antithrombotic drug which enhances prostacyclin production and activates fibrinolytic system. The aim of this study was to investigate the improvement of walking distance in patients with intermittent claudication treated with defibrotide.DICLIS was a double blind, placebo-controlled study which included patients with walking distance autonomy at a standardized treadmill test ≤350 ≥100 meters. A total of 310 patients were randomly allocated to placebo (n = 101), defibrotide 800 mg/day (n = 104) or defibrotide 1200 mg/day (n = 105).During a one year follow-up, the Absolute Walking Distance (AWD) was measured six times (0, 30, 60, 90, 180, 360 days).Similar improvement in walking distance was found in the three groups until the 90th day; thereafter placebo group showed no further increase, while AWD continued to increase in the defibrotide groups. Between the 180th and 360th day visits, AWD was significantly higher (P <0.01) in patients given defibrotide than in patients given placebo. No difference in efficacy was observed between the two dosages of defibrotide. No differences in side effects were observed among the three groups.The results of the present trial suggest that long-term administration of defibrotide improves walking distance in patients with intermittent claudication.Abbreviations: DICLIS = Defibrotide Intermittent CLaudication Italian Study, AWD = Absolute Walking Distance, IC = Intermittent Claudication, PVD = Peripheral Vascular Disease, LVOCF = Last Valid Observation Carried Forward, ITT = Intention-To-TreatAppendix, please see p. 676.
Keywords: Polydeoxyribonucleotides; fibrinolytic agents; intermittent claudication